Reliability analysis for dynamic configurations of systems with three failure modes - Pham, Hoang (Reliability engineering & system safety, 1999)
Analytical models for computing the reliability of dynamic configurations of systems, such as majority and k-out-of- n, assuming that units and systems are subject to three types of failures: stuck-at-0, stuck-at-1, and stuck-at- x are presented in this paper. Formulas for determining the optimal design policies that maximize the reliability of dynamic k-out-of- n configurations subject to three types of failures are defined. The comparisons of the reliability modeling functions are also obtained. The optimum system size and threshold value k that minimize the expected cost of dynamic k-out-of- n configurations are also determined.